Skin biopsy utilization and melanoma incidence among Medicare beneficiaries. (1st March 2017) - Weinstock, M.A.; Lott, J.P.; Wang, Q.; Titus, L.J.; Onega, T.; Nelson, H.D.; Pearson, L.; Piepkorn, M.; Barnhill, R.L.; Elmore, J.G.; Tosteson, A.N.A.
Abstract : What's already known about this topic? The persistence of stable melanoma mortality in light of increasing melanoma incidence has raised concerns that the latter may be due to 'overdiagnosis'. The ecological association between skin biopsy rates and melanoma incidence was observed for 1986–2001 but has not been examined for more recent years, resulting in important knowledge gaps. What does this study add? We find that the association between skin biopsy rates and melanoma incidence, suggestive of overdiagnosis, persists for melanoma in situ but not invasive melanoma for 2002–2009. Respond to this article Linked Comment:Watts. Br J Dermatol 2017;176 :851–852 Summary: Background: Melanoma incidence has increased in recent decades in the U.S.A. Uncertainty remains regarding how much of this increase is attributable to greater melanoma screening activities, potential detection bias and overdiagnosis. Objectives: To use a cross‐sectional ecological analysis to evaluate the relationship between skin biopsy and melanoma incidence rates over a more recent time period than prior reports. Methods: Examination of the association of biopsy rates and melanoma incidence (invasive and in situ ) in SEER‐Medicare data (including 10 states) for 2002–2009. Results: The skin biopsy rate increased by approximately 50% (6% per year) throughout this 8‐year period, from 7012 biopsies per 100 000 persons in 2002 to 10 528 biopsies per 100 000 persons in 2009. The overall melanoma incidence rate increased approximately 4% (< 1% per year) over the same time period. The incidence of melanoma in situ increased approximately 10% (1% per year), while the incidence of invasive melanoma increased from 2002 to 2005 then decreased from 2006 to 2009. Regression models estimated that, on average, for every 1000 skin biopsies performed, an additional 5·2 (95% confidence interval 4·1–6·3) cases of melanoma in situ were diagnosed and 8·1 (95% confidence interval 6·7–9·5) cases of invasive melanoma were diagnosed. When considering individual states, some demonstrated a positive association between biopsy rate and invasive melanoma incidence, others an inverse association, and still others a more complex pattern. Conclusions: Increased skin biopsies over time are associated with increased diagnosis of in situ melanoma, but the association with invasive melanoma is more complex.